STRATEGI PEMBELAJARAN PAUD MELALUI METODE DONGENG BAGI PENDIDIK PAUD - Ade Kusmiadi; Sriwahyuningsih Sriwahyuningsih; Yuyun Nurfalah (Jurnal Ilmiah Visi, 2008)
Instructional strategy is one of important factors to achieve instructional objectives. This article discusses both strengthening of Early Childhood Education (ECE) teachers in implementing instructional strategy through story telling method and some consideration upon the selection of appropriate story telling for ECE. It is one of the effective methods improving children’s competencies in many aspects. It could also improve the teachers’ knowledge and stimulate their creativity in developing learning method.